Phatic Communion in the Perspective of Language Dignity - Rahadi, R. Kunjana (Universitas Sanata Dharma, 2019)
The efforts to dignify the Indonesian language must not stop at the elaboration of grammatical rules. The Indonesian grammatical rules have long been standardized but it is still debatable whether the Indonesian language has achieved its dignity or not. As a rule, the dignified language should carry the various functions which cater to several different interests and is learned by the wider audience. The formulation of rules interconnecting with language use as in the pragmatic studies must be promoted. Essentially, the linguistic study and pragmatic study of language have the same purpose despite their different manners of doing it.Â Â